Mineralogical characterization of a polymetallic concentrate Portovelo mining district. Bioleaching by a native bacterial consortium - Gentina, J. (2009)
The mining district of Zaruma-Portovelo of southern Ecuador is a deposit of polymetallic sulfides worked since 1908. Currently the small traditional mining operation processes 1800 tons of ore a day, generating environmental waste that is accumulated and systematically discharged into the Calera and Amarillo Rivers. In this watershed area of Puyango-Tumbes, where samples were taken and subjected to gravimetric concentration, a mineralogical analysis of the concentrate was made. Samples of sediments taken from areas of weathered mining shafts were used to isolate native microorganisms for subsequent molecular and physiological characterization. The mineral concentrate contains 66.63 % of pyrite, 175 ppm Ag and 6.9 ppm Au (with 80 % of refractory gold). This mineral was subjected to biooxidation by the isolated native organisms. In experiments with pulp density of 10%, the solubility of the sulfides was very significant, reaching concentrations of Fe3 + 30 g/L and sulfate 60 g/L. © (2009) Trans Tech Publications.